Venous thromboembolism and women's health. (18th October 2018) - Speed, Victoria; Roberts, Lara N.; Patel, Jignesh P.; Arya, Roopen
Summary: The prevention and treatment of venous thromboembolism (VTE) poses distinct gender‐specific challenges. Women of childbearing age are at an increased risk of VTE secondary to the transient risk factors of combined hormonal contraception (CHC) and pregnancy. Cancers specific to women are associated with a significant burden of VTE; whilst the incidence of VTE in localised breast cancer is 5 per 1000 person‐years, more cases are seen due to the prevalence of breast cancer. Treatment of VTE in women can be complicated by abnormal uterine bleeding, now increasingly reported with direct oral anticoagulants (DOACs) as well as vitamin K antagonists. Divergence between international guidelines regarding the use of CHC following an oestrogen‐associated VTE and appropriate withdrawal of such contraception requires clarification for clinicians. Additionally, there is uncertainty as to whether to consider such events provoked or unprovoked and, consequently, the optimal duration of treatment in these women remains unclear. During pregnancy and the puerperium, the traditional anticoagulants remain the agents of choice with no further advances in DOAC safety data, and similarly in lactation. Further studies evaluating the safety and optimal treatment strategies in these women are awaited.